Predictors of COVID-19 risk perception, worry and anxiety in Italy at the end of the 2020 national lockdown. Issue 11 (2nd December 2022) - Martelletti, Corrado Paolo; Santirocchi, Alessandro; Spataro, Pietro; Rossi-Arnaud, Clelia; Löfstedt, Ragnar E.; Cestari, Vincenzo
Abstract: The present study examined the psychological predictors of four measures assessing the cognitive and emotional reactions to the COVID-19 pandemic in a sample of Italian respondents ( N = 497). Using a snowball sampling strategy, an online questionnaire was disseminated through various social media between 29th April and 29th May 2020, that is at the end of the period of national lockdown. Correlational and regression analyses indicated that a) cognitive risk was higher for participants who were younger and had direct experience with the virus; b) affective risk was higher for participants who were female, followed COVID-19-related information closely, and thought that the restrictive measures adopted by the Italian government were not sufficient; c) experienced worry was higher for participants who were female, had higher levels of prosociality and thought that the risks of COVID-19 were exaggerated; and d) state anxiety was higher for participants who were female, younger and had lower levels of prosociality. Taken together, these results support the notion that the cognitive and affective dimensions of risk perception should be analyzed as separate variables and that worry can be regarded as a construct partially independent of anxiety.